2003
DOI: 10.1177/08830738030180030801
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Preliminary Analysis of the Development of Autism and Epilepsy in Children With Infantile Spasms

Abstract: The objective of this study was to compare the efficacy of corticotropin (ACTH) versus vigabatrin in treating infantile spasms and to determine which medication has a more favorable long-term outcome in terms of cognitive function, evolution of epilepsy, and incidence of autism. Patients with infantile spasms were included in the study if they were 3 to 16 months old, had hypsarrhythmia, and had no previous treatment with vigabatrin or corticosteroids. Patient evaluation included electroencephalographic and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 31 publications
(38 reference statements)
1
45
0
4
Order By: Relevance
“…Two of the three were severely delayed in cognitive development on follow-up evaluations based on the Bayley Scales of Infant Development (the cognitive status of the third is unclear from the data). The other six patients in the cohort who did not develop ASD had, upon follow up assessment, variable cognitive outcomes, ranging from normal to significantly delayed development [68]. In a retrospective cohort of individuals with tuberous sclerosis complex (TSC)—a disorder of mTOR signaling caused by mutations in TSC1 and TSC2 and associated with IS and high prevalence rates of ASD (36%) [69]—IS occurrence predicted ASD development as determined by ICD-10 criteria in conjunction with review of ADI-R and ADOS testing [70].…”
Section: Impact Of Epilepsy On Asd In Monogenic Epileptic Encephalopamentioning
confidence: 99%
“…Two of the three were severely delayed in cognitive development on follow-up evaluations based on the Bayley Scales of Infant Development (the cognitive status of the third is unclear from the data). The other six patients in the cohort who did not develop ASD had, upon follow up assessment, variable cognitive outcomes, ranging from normal to significantly delayed development [68]. In a retrospective cohort of individuals with tuberous sclerosis complex (TSC)—a disorder of mTOR signaling caused by mutations in TSC1 and TSC2 and associated with IS and high prevalence rates of ASD (36%) [69]—IS occurrence predicted ASD development as determined by ICD-10 criteria in conjunction with review of ADI-R and ADOS testing [70].…”
Section: Impact Of Epilepsy On Asd In Monogenic Epileptic Encephalopamentioning
confidence: 99%
“…A small Class III study (n ϭ 9) comparing highdose natural ACTH with VGB 29 showed no significant difference, with all patients in both treatment arms responding. All patients had resolution of clinical spasms and hypsarrhythmia after 2 weeks of either treatment arm, although 5 of the 9 patients continued to have moderate to severely abnormal EEGs and were crossed over to the alternate drug.…”
Section: Acth Vs Vigabatrin Is Acth More Effective Than Vigabatrin Fmentioning
confidence: 99%
“…Studies have included children with or at risk for identified medical conditions/diagnoses, such as low birth weight [Msall and Tremont, 1997], birth hypoxia [Hopkins-Golightly et al, 2003], prenatal cocaine exposure [Espy et al, 1999], infantile spasms [Askalan et al, 2003], and isolated sagittal synostosis [Shipster et al, 2003], as well as inherited diseases, such as sickle-cell anemia [Gentry et al, 1997] and Fragile X syndrome [Jackson and Roberts, 1999;Kau et al, 2000]. Children identified with mental retardation [Cascella, 1999] and autism [Filipek, 1999] and children who are at risk for developmental delay [Costarides et al, 1998] have been studied extensively, using PLS-3 to assess receptive and expressive language skills.…”
Section: Examining the Impact Of Medical Conditions On Languagementioning
confidence: 99%